Synthesis, Anticancer Activities, and Mechanism of N-heptyl-containing Biguanide Derivatives - Wang, Wei; Xiao, Di; Zhou, Sichun; Xu, Simeng; Tang, Xinyi; Zhou, Xinchong; Liu, Jinbing; Xu, Cangcang; Peng, Mei; Yang, Xiaoping (Medicinal Chemistry, 2022)
Background: In recent years, the anticancer effects of biguanide drugs have received considerable attention. However, the effective concentration of biguanide drugs to kill cancer cells is relatively high. Thus, we focus on structural modification of biguanides to obtain better antitumor candidates. A previous study in our laboratory has found that a biguanide compound containing the n-heptyl group has potent anticancer activity. However, the effect of different substituents on the benzene ringside of the biguanides on the anti-proliferative activity is unknown. Objective: A series of n-heptyl-containing biguanide derivatives whose benzene rings were modified by halogen substitution based on the intermediate derivatization method were further synthesized to find new compounds with improved antiproliferative activities. Methods: Ten n-heptyl-containing biguanide derivatives were synthesized via established chemical procedures. The activities of these derivatives were explored by MTT assay, clonogenic assay, and scratch assay. The protein levels were detected via Western blotting to explore the underlying mechanisms. Results: The optimal biguanide derivatives 10a-10c, 11d exhibited IC50 values of 2.21-9.59 μ for five human cancer cell lines, significantly better than the control drug proguanil. The results of clonogenic and scratch wound healing assays also confirmed the inhibitory effects of derivatives 10a- 10c, 11d on the proliferation and migration of human cancer cell lines. Western blot results demonstrated that one representative derivative, 10c upregulates the AMPK signal pathway and downregulates mTOR/4EBP1/p70S6K. Conclusion: All biguanide derivatives containing n-heptyl groups are more active than proguanil, indicating that the modification of n-heptyl-containing biguanide derivatives provides a novel approach for the development of novel high efficient antitumor drugs.
Keywords: AMPK